Using Solvent Vapor Annealing for the Enhancement of the Stability and Efficiency of Monolithic Hole-conductor-free Perovskite Solar Cells - Thach, Lien Thi Dao; Pham, Phuc Van; Nguyen, Oanh Thi Tu; Nguyen, Hieu Si; Ta, Bach Ngoc; Pham, Long Duy; Pham, Hoi Van; Le, Chi Ha (Communications in Physics, 2020)
In the last few years, perovskite solar cells have attracted enormous interest in the photovoltaic community due to their low cost of materials, tunable band gap, excellent photovoltaic properties and easy process ability at low temperature. In this work, we fabricated hole-conductor-free carbon-based perovskite solar cells with the monolithic structure: glass/FTO/bl-TiO\(_{2}\)/(mp-TiO\(_{2}\)/mp-ZrO\(_{2}\)/mp-carbon) perovskite. The mixed 2D/3D perovskite precursor solution composed of PbI\(_{2}\), methylammonium iodide (MAI), and 5-ammoniumvaleric acid iodide (5-AVAI) was drop-casted through triple mesoporous TiO\(_{2}\)/ZrO\(_{2}\)/carbon electrode films. We found that the isopropyl alcohol (IPA) solvent vapor annealing strongly influenced on the growth of mixed 2D/3D perovskite on triple mesoscopic layers. It resulted in the better pore filling, better crystalline quality of perovskite layer, thus the improved stability and efficiency of perovskite solar cell was attributed to lower defect concentration and reduced recombination